Enantiospecific Stereospecific Strategy for the Total Synthesis of Sarpagine and Macroline Related Oxindole Alkaloids: First Total Synthesis of Affinisine Oxindole, Isoalstonisine, Alstofoline, Macrogentine, N(1)-demethylalstonisine, Alstonoxine A and Second Generation Synthesis of Alstonisine - (:unkn) unknown (My University, 2015)
The (7R)-sarpagine/macroline related oxindole alkaloids (-)-isoalstonisine (27) and (-)-macrogentine (31) together with the (7S)-sarpagine/macroline related oxindole alkaloids (-)-affinisine oxindole (24), (-)-alstonoxine A (19), (+)-alstonisine (8, second generation total synthesis), (+)-Na-demethylalstonisine (17) and (+)-alstofoline (18) were concisely synthesized during these studies. These oxindole alkaloids were isolated from plants of the genus Alstonia which is characterized by the preponderance of sarpagine/macroline-type indole and oxindole alkaloids. Plants that belong to this genus are mainly distributed over tropical regions of Central America, Africa, and Asia where they are used locally in traditional medicine, for example, in the treatment of malaria and dysentery. The main Alstonia species that have been studied in detailed to date are A. muelleriana, A. angustifolia, and A. macrophylla. A highly enantio- and diastereoselective general strategy to access the members of the sarpagine/macroline family of oxindole alkaloids was developed from cheap, com-mercially-available and optically active D-(+)-tryptophan. The built-in chirality in D-(+)-tryptophan was used and expanded, via intramolecular asymmetric induction, to form new enantio rich compounds. Although the routes were usually stereospecific any diastereomeric byproducts enabled their facile separation by methods such as column chromatography or crystallization. This only occurred in a few instances but was the reason the chirality was built in from the beginning. At the heart of this approach was the diastereospacific generation of the spiro[pyrrolidine-3,3'-oxindole] moiety at an early stage of the route via a tert-butyl hypochlorite-promoted oxidative rearrangement of chiral tetrahydro-b-carbolines derivatives. This key transformation determined the spatial configuration at the C-7 spiro center to be either R or S. Other key enantiospecific initial reactions were the asymmetric Pictet-Spengler and Dieckmann cyclization which were scalable 300-600 gram levels. This early construction of the spiro oxindole moiety had the important advantage that there was no need to perfom complex studies for every single target molecule at the end of the route which involved the optimization of reaction conditions to the particular system under study, e.g. finding the suitable oxindole-generating reaction or screening of chiral catalysts to obtain the desired stereochemistry at C-7. On the other hand, it was well-known that oxindoles at C-7 could equilibrate between 7R and 7S through a retro-Mannich process. Consequently, confirmation of the diastereomeric outcome of oxindole reactions had to be executed. As a consecuance of our studies on this topic, we were able to find a set of two reaction conditions that enabled the 7R to 7S-interconversion (and vice versa) validated by X-ray crystallography in many cases as well as 1D NOE-NMR studies. The utility of a mild Pd-promoted enolate-driven cross-coupling at room temperature, that generated the chiral center at C-14 and the Wacker-Cook oxidation process for the generation of the E-ring in the oxindole systems was demostrated. Finally, the complete structural elucidation of the final products corroborated the studies by Kam et al. who isolated these oxindole alkaloids from plants and performed their initial structure determination in many cases by X-ray crystallography.
Keywords: Alkaloids; Macroline; Oxindole; Sarpagine; Stereselective; Synthesis